Corpo feminino plus size: nomeação e/ ou condição? - Souza, Bárbara Pavei (2017)
Body and discourse walk closely in the theoretical field of the Discourse Analysis (DA), because we can comprehend as both subjectivation form (subject’s mean of constitution) and language (in this scope the art-body, for example). For the DA the body surges narrowly related to new formats of the subjectivation and, therefore, associated to the notion of ideology. More than the theoretical object, the body takes part as a dispositive of visualization as a mode of seeing the subject, its circumstances, its historicity and the culture that represent it. It is about of a body that looks at and expose itself to others eyes. Stem from these presuppositions that the feminine plus size body is thought in this dissertation. It is understandable that this body has been marked by different subject-positions as far as the discourses have been heckling and forming these subject-positions of the women, therefore, there is a necessity of nominate the fat bodies and, with that, determine their conditions of existence and visibility. The effects of the media discourses produce this feminine body, always temporary, where the woman turns to be a prisoner of an hegemonic standard of the beauty. Rooted by the theoretical notions of the Discourse Analysis, we analyzed two fashion photographies starred by plus size feminine bodies, being the first an advertising campaign of the brand Valfrance, entitled “Too hot to wear 38” and the second one, the cover of the Magazine ‘Moda Moldes’ special sizes, which has as the protagonist, the singer Preta Gil.